Hyperhalophilic archaeal biofilms: growth kinetics, structure and antagonic interaction in continuous culture - Di Meglio, Leonardo Gabriel (2014)
Biofilms by the hyperhalophilic archaea Halorubrum sp. and Halobacterium sp. were analyzed, and for the first time the progression of structural features and the developmental parameters of these sessile populations are described. Optical slicing and digital analysis of sequential micrographs showed that their three dimensional structure was microorganism dependent. Biofilms of Halobacterium sp. developed in clusters that covered about 30% of the supporting surface at the interface level and expanded over about 86 ± 4 μm in thickness, while Halorubrum sp. biofilms covered less than 20% of the surface and reached a thickness of 41 ± 1 μm. The kinetics of growth was lower in biofilms, with generation times of 27 ± 1 and 36 ± 2 h for Halobacterium sp. and Halorubrum sp., respectively, as compared to 8.4 ± 0.3 and 14 ± 1 h in planktonic cultures. Differences between microorganisms were also observed at the cell morphology level. The interaction between the two microorganisms was also evaluated, showing that Halobacterium sp. can outcompete already established Halorubrum sp. biofilms by a mechanism that might include the combined action of tunnelling swimmers and antimicrobial compounds.